Infarto agudo al miocardio. Cómo diagnosticarlo en forma precoz - Ugalde P., Héctor; Muñoz A., Macarena; Ugalde C., Diego (Revista Hospital Clínico Universidad de Chile, 2011)
Acute Myocardial infarction is the first cause of death in our country, to reduce its mortality early hospitalization is critical, so adequate treatments that have demonstrated to improve survival can be applied, particularly reperfusion therapy, that requires a diagnosis before 12 hours of evolution of symptoms to be effectively used, to do this early diagnosis two key elements are basic: clinical history and electrocardiography. This two elements are reviewed as their correct application and possible related mistakes.